Tiger's quest - Houck, Colleen (New York, N.Y. : Sterling, 2011)
Kelsey returns home to Oregon, where Mr. Kadam has enrolled her in college, but danger sends her back to India to begin another quest, this time with Kishan, to try to break the curse that forces Kisham and his brother Ren to live as tigers.
Keywords: Tigers -- Fiction; Blessing and cursing -- Fiction; Colleges and universities -- Fiction; Dating (Social customs) -- Fiction; Immortality -- Fiction; Orphans -- Fiction; Oregon -- Fiction; India -- Fiction; Young adult fiction